Modeling double-peaked spectra by combining two dimensionless JONSWAP models. (15th December 2022) - Liang, Bingxian; Sun, Zhaochen; Liang, Shuxiu; Cai, Li; Zhao, Jianchun
Abstract: Modeling a double-peaked spectrum naturally derives the significant wave heights H s 1 for the swell system and H s 2 for the wind-sea system. However, few studies have examined whether H s 1 and H s 2 are consistent with the observed significant wave heights of swell H s s and wind-sea H s w . The purpose of this research is to develop a high-precision double-peaked spectral model with the spectrum-related significant wave heights H s 1 and H s 2 that closely match the observed H s s and H s w calculated by the wind-sea and swell separation method, respectively. A novel double-peaked spectral model based on the combination of two dimensionless JONSWAP spectra is found to be advantageous over the classical GH98 model (Guedes Soares and Henriques, 1998) and the APA19 model (Akbari et al., 2019) in the applications to three field datasets of coastal China. Specifically, the present model is comparable to the APA19 model in terms of fitting accuracy but with less computation, and both are substantially superior to the GH98 model. The present model outperforms the APA19 and GH98 models regarding the correlation between spectrum-related and observed significant wave heights. Furthermore, the ordinates of the peaks of the present model are precisely consistent with those of the observed spectrum, whereas they are frequently underestimated or overestimated by the GH98 model and the APA19 model. Highlights: A novel double-peaked spectral model is proposed and confirmed effective by field data. A high-precision fit with exact match to the observed spectral peaks. Strong consistency between the observed and modeled significant wave heights.